The Parental Leave Benefit Reform in Germany: Costs and Labour Market Outcomes of Moving towards the Nordic Model - C.Katharina Spiess; Katharina Wrohlich (Population Research and Policy Review, 2008)
Germany is known to have one of the lowest fertility rates among Western European countries and also relatively low employment rates of mothers with young children. Although these trends have been observed during the last decades, the German public has only recently begun discussing these issues. In order to reverse these trends, the German government recently passed a reform of the parental leave benefit system in line with the model practiced in Nordic countries. The core piece of the reform is the replacement of the existing means-tested parental leave benefit by a wage-dependent benefit for the period of one year. In this paper we simulate fiscal costs and expected labour market outcomes of this reform. Based on a micro-simulation model for Germany we calculate first-round effects, which assume no behavioural changes and second-round effects, where we take labour supply changes into account. Our results show that on average all income groups, couples and single households, benefit from the reform. The calculation of overall costs of the reform shows that the additional costs are moderate. As far as the labour market behaviour of parents is concerned, we find no significant changes of labour market outcomes in the first year after birth. However, in the second year, mothers increase their working hours and labour market participation significantly. Our results suggest that the reform will achieve one of its aims, namely the increase in the labour market participation of mothers with young children.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s11113-008-9086-5
Keywords: 330; Female labour supply; Parental leave; Micro simulation study; Reform; Haushaltseinkommen; Kinderbetreuung